2021
DOI: 10.1007/s11071-021-06938-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal patterns in a general networked activator–substrate model

Abstract: For the purpose of understanding the spatiotemporal pattern formation in the random networked system, a general activator-substrate model with network structure is introduced. Firstly, we investigate the boundedness of the non-constant steady state of the elliptic system of the continuous media system. It is found that the non-constant steady state admits their upper and lower bounds with certain conditions. Then, one investigates some properties and non-existence of the non-constant steady state with the no-f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…So the research on the reaction-diffusion system comes into being [6,[31][32][33][34][35]. Inspired by Turing's ideas, Turing pattern on the network has developed rapidly [36][37][38]. One of the pioneering works is that Nakao and Mikhailov study Turing pattern under large random networks and found multiple steady-state coexistences and hysteresis effects [36].…”
Section: Introductionmentioning
confidence: 99%
“…So the research on the reaction-diffusion system comes into being [6,[31][32][33][34][35]. Inspired by Turing's ideas, Turing pattern on the network has developed rapidly [36][37][38]. One of the pioneering works is that Nakao and Mikhailov study Turing pattern under large random networks and found multiple steady-state coexistences and hysteresis effects [36].…”
Section: Introductionmentioning
confidence: 99%